IMPROVING LAND MANAGEMENT OF RECLAIMED LANDS - Mykula , О.; Susak , М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
An analysis was conducted on the changes in regulatory and methodological support for land management in Ukraine. The key updates pertain to the types of land management documentation as specified by the Law of Ukraine "On Land Management." Notably, this law has removed national and regional programs for land use and protection, as well as certain land management projects, and introduced new regulations regarding land tenure and land use. The study identified shortcomings in the project development system at national, regional, and local levels, particularly in relation to the actual state of reclaimed lands and the potential for expanding these areas. It also highlighted issues with urban planning documentation - such as comprehensive plans for territorial community development, master plans for settlements, and detailed territorial plans - which fail to account for the irrigation and drainage strategies approved by the Government of Ukraine and the broader development plan for the irrigation complex. To improve this situation, it is recommended that state-level territorial planning documents incorporate the General Scheme of Planning for the Territory of Ukraine as well as planning schemes for individual regions, districts, and the Autonomous Republic of Crimea. There is also a call to reinstate the development of national and regional programs for land use and protection. These documents should address the development of hydrotechnical, cultural, agrotechnical, chemical, and agroforestry land reclamation efforts. They must identify specific areas that require targeted land reclamation measures and outline the necessary steps for developing working land management projects as part of the comprehensive plans for spatial development of territorial communities. The primary focus should shift away from merely engineering protections of territories and instead prioritize measures to preserve and enhance soil fertility through various types of land reclamation. This comprehensive approach will help address the challenges of organizing land use and protection effectively.